2021
DOI: 10.1016/j.ultsonch.2021.105529
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage continuous production process for fatty acid methyl ester from high FFA crude palm oil using rotor-stator hydrocavitation

Abstract: Highlights Hydrosonic and ultrasonic reactors were compared in two-step biodiesel process. Key part is utilizing the 3D-printed rotor–stator. Methyl ester 99.163 wt% was produced using rotor–stator hydrodynamic reactor. Maximum yields 97.51 vol% purified biodiesel was achieved using HC reactor. The total average energy consumption of using HC reactor was 0.049 kW h/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
(36 reference statements)
0
20
0
Order By: Relevance
“…(2011) [34] , and Oo et al . (2021), who mentioned that hydrodynamic cavitation is an alternative to acoustic cavitation, as it is suitable for industrial mass production [33] . Furthermore, the rotor-stator type of reactor is particularly well suited for industrial applications owing to the extensive utilization of the cavitation zone, low cost of equipment, and ease of scaling [35] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2011) [34] , and Oo et al . (2021), who mentioned that hydrodynamic cavitation is an alternative to acoustic cavitation, as it is suitable for industrial mass production [33] . Furthermore, the rotor-stator type of reactor is particularly well suited for industrial applications owing to the extensive utilization of the cavitation zone, low cost of equipment, and ease of scaling [35] .…”
Section: Resultsmentioning
confidence: 99%
“…The rotating part of the 3D-printed rotor was fabricated with polylactic acid using a high-performance 3D printer (model: Creator3, Flashforge, Zhejiang, China). The printing cost of this 3D-printed rotor is quite low, at approximately 2 USD, and thus, this processing technique has the potential to be both cost-effective and time-efficient [33] . In a previous study, long-lasting stainless steel rotors with many holes on their surfaces, manufactured using a computer numerical control machine, were recommended for the practical industrial process of biodiesel production.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These optimized conditions have the potential to reduce the FFA concentration in LGPO from 20% to less than 3% under optimal conditions. 9 Mohod et al 17 also reported that biodiesel could be synthesized from karanja oil using acoustic cavitation. The acid value of 14.15 mgKOH/g of karanja oil was reduced to less than 2.7 mgKOH/g at the optimal condition of 5:1 methanol to oil ratio and 2% H 2 SO 4 concentration at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Second-generation feedstock biofuel is a nonedible substance derived from waste and byproducts of the palm oil refining plant. These raw materials can be used effectively to produce biodiesel because they can supply a greater amount of biofuel sustainably and at a cheaper cost than crude palm oil, which is the main raw material used to produce biodiesel in Thailand and Asian countries. , According to a global report on the estimated amount of crude palm oil (CPO) production, worldwide CPO production in 2021 was approximately 75.45 million tons. It is difficult to find an official production rate of PFAD.…”
Section: Introductionmentioning
confidence: 99%